The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2174/138955708784912148
|View full text |Cite
|
Sign up to set email alerts
|

Natural Marine Anti-inflammatory Products

Abstract: The marine environment has been shown to be the source of a great diversity of chemical structures with promising biological activities. The isolation, biological evaluation, chemical properties and synthetic elaborations of the products of marine organisms and microorganisms have attracted the attention of organic chemists, medicinal chemists, biologists and pharmacists. Marine organisms and microorganisms have provided a large proportion of the natural anti-inflammatory products over the last years. Marine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…in order to survive. Their economic potential is important in some areas of the globe, with Asia considering them as a central part of their diet (wakame, kombu) and Europe using them as a source of fertilizers, cosmetics, pharmacological products, and defense elicitors (Klarzynski et al, 2000;Abad et al, 2008;Holtkamp et al, 2009).…”
mentioning
confidence: 99%
“…in order to survive. Their economic potential is important in some areas of the globe, with Asia considering them as a central part of their diet (wakame, kombu) and Europe using them as a source of fertilizers, cosmetics, pharmacological products, and defense elicitors (Klarzynski et al, 2000;Abad et al, 2008;Holtkamp et al, 2009).…”
mentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have documented with anti-oxidant and anti-inflammatory activities of marine algae. 32 Ecklonia cava (Phaeophyceae; Laminareaceae), also known as ''sea trumpet", has been reported to possess anti-inflammatory activity. 33 E. cava was also able to suppress the levels of pro-inflammatory mediators such as nitric oxide (NO), prostaglandin-E2 (PGE2) and pro-inflammatory cytokines such as interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α).…”
Section: Biochemical Action Of Neuroprotective Marine Algaementioning
confidence: 99%
“…In marine research, it is found that some natural products contain antioxidants with anti-inflammatory activities [29]. A compound isolated from green algae, Dunaliella bardawil (rich in b-carotene), had shown protective effects against acetic-acid-induced small bowel inflammation in rats [30].…”
Section: Anti-inflammatory Assaysmentioning
confidence: 99%